Pengaruh Lama Simpan Susu Pasteurisasi Rasa Coklat pada Suhu Dingin Terhadap Total Asam dan Kualitas Organoleptik (Rasa, Tekstur, Aroma) - Unggul Dzaky Adriawan; Triana Setyawardani; Agustinus Hantoro Djoko Rahardjo (ANGON: Journal of Animal Science and Technology, 2021)
Background. This study aimed to determine the effect of shelf life of chocolate flavored pasteurized milk at cold temperatures on total acid and organoleptic quality (taste, texture, aroma). The research was conducted at the Laboratory of Animal Husbandry Product Technology, Faculty of Animal Husbandry, Jenderal Soedirman University, Purwokerto. Materials and methods. The research was conducted using the RAK experimental method and the organoleptic variables used the RAL method. Treatment that has an effect will be further tested by DMRT. The treatments tested were storage time of 0, 3, 6, 9, 12 days, the measured variable was the total titrated acid level, tested the level of preference for aroma, taste, and texture. Results. The results of analysis of variance showed that storage time had no significant effect (P> 0.05) on total acid. The total acid content was 1.77 - 2.27%. During storage of pasteurized milk, the taste of chocolate had a significant effect (P <0.05) on the level of liking for aroma and texture, but had no significant effect (P> 0.05) on the level of taste preference. The results of the study the effect of storage time on quality and preference on taste had an average value of 12 days = 2.60 ± 1.62 and at 3 days treatment = 3.23 ± 1.15. The results on the quality and level of preference for the texture mean value at 12 days treatment = 2.93 ± 1.44 and the mean value at 0 days treatment = 3.73 ± 0.89. The results showed that the panelists' preferred level of aroma with the lowest average value on the 6 days treatment = 2.70 ± 1.25 and the highest average value at 0 days treatment = 3.56 ± 1.01. The total concentration of titrated acid did not change, the average value was 2.02%. Conclusion. Before and during storage, the liking for the taste quality did not change, the liking for the aroma quality and the texture decreased.